Впровадження нових дисциплін у навчальний процес - Беззубко, Борис Ігорович; Шумейко, Іван Павлович; Юник, Ірина Геннадіївна; Коломієць, Сергій Сергійович; Свистун, Олександр Іванович; Bezzubko, Borys; Shumeiko, Ivan; Yunyk, Iryna; Kolomiiets, Serhii; Svystun, Oleksandr (Запоріжжя : ТДАТУ, 2026)
UA: Обґрунтована необхідність впровадження нових навчальних дисциплін у процес підготовки фахівців з управління та економіки. Розкрито зміст основних етапів алгоритму впровадження нових дисциплін у навчальний процес. Визначено основні чинники, які зумовлюють необхідність введення в навчальний процес нових дисциплін. Підкреслено впливи цифровізації; розвитку економічної науки та управлінських практик; законодавчих і регуляторних зміни в суспільстві; розповсюдження вимог і принципів сталого розвитку на процеси впровадження нових навчальних дисциплін. /// EN: The paper justifies the need to introduce new academic disciplines into the training process for specialists in management/and economics. It outlines the main stages of the algorithm for introducing new disciplines into the educational process. The key factors that determine the need to introduce new disciplines into the educational process are identified. The article highlights the impact of digitalization; the development of economic science and management practices; legislative and regulatory changes in society; and the spread of the requirements and principles of sustainable development on the processes of introducing new academic disciplines.
Introduction of new disciplines into the educational process
Keywords: освітній процес; вища школа; навчальні дисципліни; підготовка економістів і менеджерів; educational process; higher education; academic disciplines; training of economists and managers